2014
DOI: 10.1007/s00894-014-2247-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics, dynamic site mapping, and highthroughput virtual screening on leptin and the Ob receptor as anti-obesity target

Abstract: Body weight control is a mechanism finely regulated by several hormonal, metabolic, and nervous pathways. The leptin receptor (Ob-R) is crucial for energy homeostasis and regulation of food uptake. Leptin is a 16 kDa hormone that is mainly secreted by fat cells into the bloodstream, and under normal circumstances, circulating levels are proportionate to the fat body mass. Sensing of elevated leptin levels by the hypothalamic neurocircutry activates a negative feedback loop resulting in reduced food intake and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…In the crystal structure, the JK loop adopts two different conformations, and this conformational flexibility may suggest that leptin binding to CRH2 involves an induced fit mechanism [15]. Finally, structural insights in the leptin:CRH2 binding could allow virtual docking screening for compounds with potential agonistic or antagonistic potential [121].…”
Section: The Crh2 Domain As the Leptin Binding Determinantmentioning
confidence: 98%
See 1 more Smart Citation
“…In the crystal structure, the JK loop adopts two different conformations, and this conformational flexibility may suggest that leptin binding to CRH2 involves an induced fit mechanism [15]. Finally, structural insights in the leptin:CRH2 binding could allow virtual docking screening for compounds with potential agonistic or antagonistic potential [121].…”
Section: The Crh2 Domain As the Leptin Binding Determinantmentioning
confidence: 98%
“…Follow-up in vitro experiments and studies in db/db mice showed that these effects do not require interaction with the LR long form. Nonetheless, LEP- (116)(117)(118)(119)(120)(121)(122)(123)(124)(125)(126)(127)(128)(129)(130) was proven to promote luteinizing hormone (LH) and prolactin (PRL) secretion in fasted animal rats [49].…”
Section: Leptin Peptide Modulatorsmentioning
confidence: 99%
“…MD simulations have proved to be invaluable for understanding the dynamics of biomolecules and solvent effects; furthermore, MD simulations form the basis of advanced techniques such as the calculation of free energies of protein–ligand binding . The use of MD simulations prior to the virtual screening process has been demonstrated to be very helpful for retrieving information about protein conformations or ligand–protein interaction dynamics . Analyzing the interaction pattern of ligands with a specific protein target has a strong bias toward the molecular structure of the ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity has become the most frequent pathology related to the nutrition in many countries; it is regarded as a major problem of public health . The body weight control is a mechanism finely regulated by several hormonal, metabolic, and nervous pathways . In chronically overweight, the problem is that the action of certain hormones (leptin, adiponectin …) is blocked and does not contribute to reduce appetite and to stimulate fat oxidation .…”
mentioning
confidence: 99%
“…Key words: antioxidant enzymes, bisphosphonates, free radicals, lipases, obesity, oxidative stress, pH-stat technique Received 29 September 2014, revised 18 November 2014 and accepted for publication 24 November 2014 Obesity has become the most frequent pathology related to the nutrition in many countries; it is regarded as a major problem of public health (1). The body weight control is a mechanism finely regulated by several hormonal, metabolic, and nervous pathways (2). In chronically overweight, the problem is that the action of certain hormones (leptin, adiponectin .…”
mentioning
confidence: 99%